Depictions of the Priest, the Liberal Guerrilla and the Police in Lo que el cielo no perdona - Rosa Carolina Gil Jaramillo (Historia y Sociedad, 2018)
Lo que el cielo no perdona is a novel written by Colombian priest Fidel Blandón Berrío that is inscribed in the so-called la Violencia literature or la Violencia novel categories. The novel is interpreted as a testimony of the author’s experiences in western Antioquia while defending the liberal guerrillas settled near to the township of Juntas. This article reconstructs aspects of the priest’s life and of his depiction in the novel, as well as those of the liberal guerrilla and the police, in order to rescue a character that has been understudied in the historiography of la Violencia and who sought peace in a highly polarized and belligerent context. The analysis concludes by showing that Blandón Berrío opposed the incendiary anti-liberal discourses of other priests and the arguments of those who upheld belonging to the Catholic religion as sufficient evidence for the exoneration from crimes committed during la Violencia period.